mSphere of Influence: The challenge of screening for essential protein kinases in Trypanosoma cruzi - Miguel A. Chiurillo (mSphere, 2025)
ABSTRACT Miguel Chiurillo works in the field of protein kinases, studying their role in cell signaling and cell cycle progression in Trypanosoma cruzi. In this mSphere of Influence article, he reflects on how the research articles “Systematic functional analysis of Leishmania protein kinases identifies regulators of differentiation or survival” by Baker et al. and “Screening the Toxoplasma kinome with high throughput tagging identifies a regulator of invasion and egress” by Smith et al. made an impact on his understanding of the complexity of the Trypanosoma cruzi kinome and the challenges to unravel it.